Recurrent Ectopic Pregnancy in the Tubal Remnant after Salpingectomy - Bahareh Samiei-Sarir; Christopher Diehm (Case Reports in Obstetrics and Gynecology)
We present two cases of ectopic pregnancy located within the remnant tube following ipsilateral salpingectomy. This particular pathology is rare and yet has significant consequences for the patient, with mortality rates 10–15 times higher than other ectopic pregnancies. It demonstrates that salpingectomy does not exclude ectopic pregnancy on the ipsilateral side. We suggest careful clinical consideration and bring attention to the current surgical technique.